Cooperative secret key generation for multi-hop relaying systems in Internet of things - Shuaifang XIAO; Yunfei GUO; Kaizhi HUANG; Liang JIN (Tongxin xuebao)
The achievable key rate of secret key generation method in multi-hop relaying systems was relative low in Internet of things.A cooperative secret key generation algorithm based on network coding was proposed to improve the achievable key rate.Firstly,all the nodes send training sequences in turn to estimate the channels.After that the relays employ secure network coding technique to assist the two legitimate users to obtain the correlative observations of the same wireless channel,with nothing leakage about the channel information to the eavesdropper.Finally,the two legitimate users agreed on a common secret key directly over the public channel.Theoretical and simulation results validate the performance of the proposed secret key generation algorithm,and obtain that increasing the wireless transmission paths,selecting the transmission path with less hops and larger variance channels can further improve the achievable secret key rate.